If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -24 = x + -5 Reorder the terms: -24 + 6x = x + -5 Reorder the terms: -24 + 6x = -5 + x Solving -24 + 6x = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -24 + 6x + -1x = -5 + x + -1x Combine like terms: 6x + -1x = 5x -24 + 5x = -5 + x + -1x Combine like terms: x + -1x = 0 -24 + 5x = -5 + 0 -24 + 5x = -5 Add '24' to each side of the equation. -24 + 24 + 5x = -5 + 24 Combine like terms: -24 + 24 = 0 0 + 5x = -5 + 24 5x = -5 + 24 Combine like terms: -5 + 24 = 19 5x = 19 Divide each side by '5'. x = 3.8 Simplifying x = 3.8
| 4.9x^2+24x-13=0 | | x=5+0.5x | | y=ln61(11/x) | | 2x+14=x-5 | | hbt=2pifort | | 8(t-2)+6t=7(2t+4)-9 | | -8u+5(u-5)=-4 | | 2=2(m-8)-5 | | 3p+2=11+2p | | 9(4x-3)=3(12x+9) | | -4+(2x^2)=x+7 | | 4+(2x^2)=x+7 | | y=-8-8 | | -4x-y=12 | | x-5y=16fory | | 13x-5=2x-71 | | 9(x+5)-(2x-3)=3 | | 129=2x^2-41x | | 1/5y-2/9=1/9y-6/5 | | -7.2x^2-33.1x+18.3=0 | | U/3-3.1=-7.9 | | 2x+6=3(9-x) | | -5=5/8n | | 14z=9z-5+4z | | 109+5x=119+4x | | 1/4y-3/7=1/7y-9/4 | | 15x-7=8x-56 | | 8(x+1)-(5x-6)=6 | | 5(3n-3)=6(8+n) | | (x/3)-(x/4)=(7/4) | | (5x-4)(x+10)=7 | | 8-8x-6-4x=5 |